Communication systems - Haykin, Simon S. (Wiley, 2001)
Background and preview - Random processes - Continous-wave modulation - Pulse modulation - Baseband pulse transmission - Signal-space analysis - Passband digital transmission - Spread-spectrum modulation - Multiuser radio comunications - Fundamental limits in information theory - Error-control coding - Appendices.